Seed dispersal disruption limits tropical forest regrowth - Evan C. Fricke; Susan C. Cook-Patton; Charles F. Harvey; Cesar Terrer (Proceedings of the National Academy of Sciences, 2025)
Identifying linkages between biodiversity loss and climate change is required for understanding the scope of these interconnected challenges and developing approaches to address them. One crucial yet underexplored aspect is the influence of seed-dispersing animals on forest carbon storage. Here, we show that 81% of tropical trees rely on animals for seed dispersal and that disruption of this process, due to declines in animal diversity and movement, significantly hampers the carbon accumulation potential of regrowing tropical forests. Using a synthesis of animal biodiversity, movement, and seed dispersal data covering thousands of animal species, we developed an index of seed dispersal disruption and modeled its relationship to carbon accumulation observed across 3,026 tropical regrowth plots. Naturally regrowing areas with lowest seed dispersal disruption had aboveground carbon accumulation rates four times higher than those with most severe disruption. Across areas identified as locations suitable for reforestation, current levels of seed dispersal disruption yield a 57% average reduction in local carbon accumulation potential. Tropical regrowth forests currently represent the largest land-based carbon sink; ongoing animal biodiversity losses diminish their ability to recover naturally from disturbances and therefore threaten their climate mitigation potential. These results advance understanding of animal biodiversity’s impact on carbon dynamics and emphasize the need to address biodiversity loss and climate change together.